Great Power Rivalry in a New Asia Pacific Order: Examining the Great Power Concert Model for Asia Pacific - Anam, Syaiful (Jurnal Hubungan Internasional, 2014)
Chinaâs rising power in the Asia Pacific region is leading the regional order to face a potential of rivalry between existing great powers in the region. This paper hence seeks to investigate the great power rivalry in a new Asia Pacific order. It argues that while âthe European great power concert modelâ, as proposed by Hugh White (2008), could potentially be a mechanism for maintaining peace and stability in the Asia Pacific region, it has considerable problems and obstacles to be applied in the region.